2022
DOI: 10.15376/biores.17.2.cao
|View full text |Cite
|
Sign up to set email alerts
|

Research progress and prospects of wood high-temperature heat treatment technology

Abstract: High temperature heat treatment is one of the main technologies with the highest market conversion rate and broad future prospects in the functional technology of wood. Chemical reagents are not added in the production process. The treatment improves the dimensional stability, biological durability, wood color, and acoustic properties without reducing the environmental performance of the product. However, there are some problems in heat treatment, such as the reduction of mechanical properties and surface wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This research revealed that CA impregnation could degraded some chemical components of wood (Cao et al, 2022;Esteves and Pereira, 2009;Schulz et al, 2021). This degradation increased samama wood's durability against fungal attacks.…”
Section: Durability Against Brown-and White Rotmentioning
confidence: 93%
“…This research revealed that CA impregnation could degraded some chemical components of wood (Cao et al, 2022;Esteves and Pereira, 2009;Schulz et al, 2021). This degradation increased samama wood's durability against fungal attacks.…”
Section: Durability Against Brown-and White Rotmentioning
confidence: 93%
“…The changes in the chemical components of BOSB with increasing thermal treatment duration caused the adhesive between strands to become brittle, thereby reducing the IB strength values of BOSB. Cao et al (2022) stated that thermal treatment of wood reduced the ability of the wood to resist cracks or pores when tensile loads are applied. It is due to the increased brittleness of thermally-modified wood.…”
Section: Internal Bonding Strengthmentioning
confidence: 99%
“…Speaking of heat treatment, it has the highest market conversion rate and broad future prospects in the functional technology of wood [ 18 ], which is why this treatment has been the subject of numerous studies. Indeed, studies on certain wood species have shown that heat treatment of wood with steam reduces swelling and shrinkage and lowers its equilibrium moisture content [ 19 ].…”
Section: Introductionmentioning
confidence: 99%